Percutaneous transgastrostomic interventional radiology-operated endoscopy facilitates foreign body removal using rigid endobronchial forceps - Mamdouh Khayat; Jawad S. Hussain; Jeffrey Forris Beecham Chick; Anthony N. Hage; Ravi N. Srinivasa (Diagnostic and Interventional Radiology, 2018)

(untitled)
Retained foreign bodies within the stomach and proximal small bowel may be problematic in patients with prior cerebrovascular injury or head, neck and esophageal malignancy, given the increased vulnerability of this patient population to complications from aspiration and increased difficulty of esophagogastroduodenoscopy in cases of tumoral obstruction. This article presents an alternative method for foreign body retrieval through an existing gastrostomy tract, which offers the benefits of fast procedure times, reduction in radiation dose and fluoroscopy time, and allows for safer retrieval of foreign bodies by using direct visualization. This technique may be performed entirely by interventional radiologists.